Organizacja działań ratowniczych podczas zdarzeń drogowych - Konieczny, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The Polish law regulations determine the rescue operations during road incidents in many aspects. These provisions relate to the obligations of the owner and manager of the road on which the incident took place. These provisions also include the obligations of the participant of the rescue action. Special regulations apply to chemical and environmental dangers.
Keywords: działania ratownicze; zdarzenia drogowe; uczestnicy akcji ratunkowej